2021
DOI: 10.3389/fpsyg.2021.706601
|View full text |Cite
|
Sign up to set email alerts
|

Increases in Anxiety and Depression During COVID-19: A Large Longitudinal Study From China

Abstract: Although accumulating evidence suggests the COVID-19 pandemic is associated with costs in mental health, the development of students' mental health, including the change from their previous levels of depression and anxiety and the factors associated with this change, has not been well-studied. The present study investigates changes in students' anxiety and depression from before the pandemic to during the lockdown and identifies factors that are associated with these changes. 14,769 university students partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 70 publications
0
32
1
1
Order By: Relevance
“…Women, younger individuals, and the older adults are more vulnerable in this pandemic. In another comprehensive longitudinal study, Wu et al ( 12 ) reported increased anxiety and depressive symptoms among Chinese people.…”
Section: Introductionmentioning
confidence: 97%
“…Women, younger individuals, and the older adults are more vulnerable in this pandemic. In another comprehensive longitudinal study, Wu et al ( 12 ) reported increased anxiety and depressive symptoms among Chinese people.…”
Section: Introductionmentioning
confidence: 97%
“…Orlov et al (2021) similarly described that students performed, on average, worse during the pandemic than during previous semesters. Concerning students stress perceptions, the results are not that clear: Whereas some studies found that stress and anxiety perceptions generally increased (see, e.g., Limcaoco et al, 2020;Wu et al, 2021;, some work showed that academic stress first increased but then decreased to pre-COVID levels (see, e.g., Charles et al, 2021). Other studies even yielded that studying during COVID-19 had no effects on students' stress perceptions triggered by learning processes (see, e.g., de la Fuente et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, challenges regarding learning, interpersonal relations, and the future were different from those of the other groups. According to the literature [ 18 , 35 , 36 ], the reasons for the aforementioned changes in social mentality could be anxiety and insecurity caused by risk perception in disease outbreaks, loneliness, and helplessness elicited by isolation and social distancing, maladaptation to online learning, tremendous employment pressure in a disrupted job market, tension with families during home quarantine, the reopening of schools affecting students with fundamental psychological problems, and constantly receiving negative information about the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study by Wu S.Z. et al focused on changes in students’ mental health in response to the pandemic and local factors’ role in these changes [ 18 ]. The results from the research above provided strong evidence for the knowledge of students’ mental health and the implementation of psychological interventions during the pandemic.…”
Section: Introductionmentioning
confidence: 99%